2018
DOI: 10.24200/sci.2018.20334
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanical and Durability Properties of Concrete Containing PET Waste

Abstract: Plastic waste is a silent threat to the environment, and their disposal is a serious issue. To sort out this issue, many efforts were made to reuse the plastic waste, but no significant results were achieved. On the contrary, concrete being the widely used construction material is facing problem due to unavailability of ingredient material (sand and coarse aggregate). In this study PET (polyethylene terephthalate) aggregates manufactured from the waste un-washed PET bottles in shredded form were used to partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…Similar to our findings, studies have demonstrated that adding RHA 95 , 105 107 , NS 41 , 108 110 , and NA 103 , 111 to concrete reduces chloride ion penetration and water absorption. Furthermore, adding nano to RHA-enriched cement mortars improved the composite’s chloride resistance 112 , while adding polyethylene terephthalate aggregates increases the depth of water penetration 113 . Moreover, adding of fly ash and coal gangue decreased the chloride diffusion coefficient 114 .…”
Section: Resultsmentioning
confidence: 99%
“…Similar to our findings, studies have demonstrated that adding RHA 95 , 105 107 , NS 41 , 108 110 , and NA 103 , 111 to concrete reduces chloride ion penetration and water absorption. Furthermore, adding nano to RHA-enriched cement mortars improved the composite’s chloride resistance 112 , while adding polyethylene terephthalate aggregates increases the depth of water penetration 113 . Moreover, adding of fly ash and coal gangue decreased the chloride diffusion coefficient 114 .…”
Section: Resultsmentioning
confidence: 99%
“…The studies done by previous studies at 20% replacement of natural river sand with PET waste revealed a 75%, 5%, and 28% reduction in compressive strength [102][103][104]. However, the variation in strength was seen in different studies, and trends show precise observation of declining strength at a higher replacement ratio of up to 20%.…”
Section: Figure 5 Relative Compressive Strength Variation With Pet Pe...mentioning
confidence: 89%
“…Saxena et al [31] observaron que la profundidad de penetración del agua para una relación de 0:45 a/c sin residuos de PET después de 28 días de curado era de 24 mm y aumentaba con el incremento de residuos PET en el concreto. También observaron que eran de 24 mm, 28 mm, 42 mm, 71 mm y 105 mm en remplazos del 0 %, 5 %, 10 %, 15 % y 20 % de agregado.…”
Section: Permeabilidadunclassified